Internal voids as a stress reliever and palliative in fretting fatigue. (2018) - Erena, Diego; Vázquez, Jesús; Navarro, Carlos; Domínguez, Jaime
Abstract: Currently, additive manufacturing with metals is an increasingly popular technique that allows the manufacturing of pieces of difficult shapes, nearly impossible to make with other techniques. Usually, these shapes try to optimize the solid to have the same strength with a lower weight. The fatigue behavior of the material of the components manufactured with this technique is a field in development. On the other hand, fretting fatigue is a common type of fatigue where a "stress concentration" appears due to the contact between two components. There are some procedures used to increase fatigue life in this situation (shot peening, surface knurling, etc.). This paper tries to analyze the possible beneficial effect on fatigue life of introducing voids inside the material in components under fretting, which is feasible now thanks to additive manufacturing. The problem under study is, for now, a 2D simplification where a cylinder is in contact with a half plane and a normal constant load and a variable tangential load are applied. This geometry has been numerically simulated, introducing a circular hole below the surface. The effect of this hole is to make the contact more elastic, which decreases the stresses near the surface. This work analyses and compares the stress and strain fields and Smith-Watson-Topper multiaxial fatigue parameter in the areas sensitives to fretting with respect to a case with homogeneous material (no internal voids). Various configurations changing different parameters like size and position of the hole, friction coefficient and the size of the slip zone have been considered. The problem analyzed in this paper is two-dimensional, therefore there would be no need to use additive manufacturing in a real situation. However, the results obtained in this paper indicate that it could also work in 3D. Actually, it is in a real three-dimensional problem where the additive manufacturing would be necessary for the introduction of voids inside the material to improve fatigue life.